Photochemistry and absorption cross-sections temperature dependence of trifluoromethoxycarbonyl peroxy nitrate (CF3OC(O)OONO2) - Malanca, Fabio Ernesto (2009)
The photochemical rupture of CF3OC(O)OONO2 at 254 nm leads to the formation of NO2 + CF3OC(O)OO, and NO3 + CF3OC(O)O radicals. The study carried out at 297, 273 and 253 K leads to a quantum yield φsymbolN O3 = 0.18 ± 0.03, and φsymbolN O2 + φsymbolN O3 = 1.01 ± 0.09. To minimize the errors in both the determination of quantum yields and the analysis of atmospheric photochemical lifetimes, the study of the absorption cross-sections dependence with temperature between 297 and 245 K was undertaken. There is a clear increase of the cross-sections with temperature. The atmospheric photochemical lifetime of CF3OC(O)OONO2 and its comparison with thermal decomposition are presented. © 2009 Elsevier B.V. All rights reserved.